2006
DOI: 10.1007/s00261-006-9017-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the pancreas. 2. Harmonic imaging

Abstract: Tissue harmonic imaging (THI) is a relatively new ultrasonographic imaging modality which has been implemented in many modern scanners. As several previous studies have pointed out, THI can help to overcome some shortcomings of conventional B-mode ultrasonography (US). The aim of this article is to give a compact summary of the potentials of THI, focused on pancreatic imaging. Beginning with a recapitulation of the technical background of THI, the particularities and suitable applications of THI in US of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Nonfunctioning neuroendocrine tumors present as large, well-marginated hypoechoic masses, usually easy to detect, thanks to their large size, which also justifies their tendency to contain necrosis and hemorrhage, giving them a typical inhomogeneous appearance at imaging [2,15,22].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Nonfunctioning neuroendocrine tumors present as large, well-marginated hypoechoic masses, usually easy to detect, thanks to their large size, which also justifies their tendency to contain necrosis and hemorrhage, giving them a typical inhomogeneous appearance at imaging [2,15,22].…”
Section: Ultrasoundmentioning
confidence: 99%
“…In pancreatic imaging, it has been shown that THI provides an enhanced overall image quality, better lesion conspicuity and advantages in solid-cystic differentiation in comparison to the conventional BM ultrasound. [4] In previous studies THI has been proven to be superior in ultrasound of the heart, vascular system, liver, biliary system, kidneys and female pelvis because harmonic imaging show a superior image quality, fewer artifacts and better delineation of normal and pathological structures compared with B-mode ultrasound. [9][10][11][12][13] Tanka et al, [13] showed that THI was significantly better in detecting and correctly characterizing focal masses of the liver than with BM ultrasound, especially for hepatocellular carcinoma in cirrhotic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…[4] A new approach to combat the inherent limitations of conventional ultrasound is tissue harmonic imaging. These harmonic beams are whole-numbered multiples of a fundamental frequency that are transmitted by an ultrasound probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, sometimes, the lesion can be diffi cult to identify or delineate. Harmonic US and compound techniques may improve the correct identifi cation of the margins of the tumor [ 29 ].…”
Section: Ultrasoundmentioning
confidence: 99%